COOLING OF SOLAR PV PANELS USING EVAPORATIVE COOLING - Haidar, Zeyad A.; Orfi, J.; Öztop, Hakan Fehmi; Kaneesamkandi, Z. (Yildiz Technical Univ, 2016)
The efficiency of solar collection systems particularly the photovoltaic panels is generally low. This is due to several reasons including dust formation and thermal losses. For instance, the PV panels efficiency is affected by the increase of their surface temperature. This increase is associated with the absorbed solar radiation that is not converted into electricity causing a drop in the PV module efficiency. Several cooling methods are available to reduce the cells temperature and their respective effectiveness has been investigated in several previous works. This study deals with PV panels cooling using evaporative cooling of water. A theoretical model based on the heat and mass transfer occurring in the vicinity of the bottom side of a solar PV panel has been developed. The model incorporates the heat and mass exchange occurring between a layer of water and ambient air as well as the heat transfer with the PV panel. The obtained results show the effect of some geometrical parameters as well as the air flow rate, temperature and humidity on the cooling process. It was found in particular that when the air inlet temperature decreases, the temperature of the PV panel decreases significantly.
Keywords: PV panel; cooling; evaporation; modelling